Reasons of Refusal to Long Acting Reversible Contraception (LARC) on Reproductive Age Women: a Scoping Review - Biancha Andardi; Ditia G. S. P. Rahim; Anhari Achadi (Universitas Sam Ratulangi, 2022)
Abstract: Contraception is essential in reproductive health service. Through proper contraception, various risks related to pregnancy and birth can be avoided. Long acting reversible contraception (LARC) is deemed as the most efficient contraceptive metod. However, it faces significant refusal among women worldwide. This study aimed to determine the reason of LARC refusal among reproductive age women. A scoping review was done using a guideline from Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) on studies performed on Asian developing countries. The results showed that a total of seven articles were analyzed. The most common reason for LARC refusal was the disagreement of husband or other family members. Prior knowledge of LARC might increase the acceptance of LARC. In conclusion, since the most common reason for LARC refusal was the disagreement of husband or other family members, education of LARC method on pregnant women, their spouses, and their families is essential to reduce that rate of LARC refusal.Keywords: contraception; long acting reversible contraception; refusal